Phase Interferometry for Approach Radars - Zálabský, Tomáš; Bezoušek, Pavel (Croatian Society Electronics in Marine - ELMAR, 2017)
This paper discusses the design of an interferometric system that the role of a passive precision approach radar should perform. The brief overview of requirements for precision approach radar parameters is presented. The proposal of an interferometric system for a multi-base phase interferometer is described. An evaluation of the accuracy of determining the angle of arrival of the incident signal is described. Models of standard deviations of a determine the angle of arrival of the incident signal, depending on the individual system parameters are determined. The impact of ground reflection on the signal is discussed. Finally, the results of these models are discussed and a proposal for minimum requirements for the deployment of individual phase interferometer receivers is made.
Fázový interferometrycký systém pro precizní přistávací radar
Keywords: Phase Interferometry, Precision Approach radar, Radar, Reflection from the terrain; Fázový interferometr, Precizní přistávací radar, Radar, Odraz signálu od země